Assessment of Endoscopic Healing by Using Advanced Technologies Reflects Histological Healing in Ulcerative Colitis. (23rd March 2020) - Iacucci, Marietta; Cannatelli, Rosanna; Gui, Xianyong; Zardo, Davide; Bazarova, Alina; Gkoutos, Georgios V; Lethebe, Brendan Cord; Kaplan, Gilaad G; Panaccione, Remo; Kiesslich, Ralf; Ghosh, Subrata
Abstract: Background: Several studies have reported that ulcerative colitis [UC] patients with endoscopic mucosal healing may still have histological inflammation. We investigated the relationship between mucosal healing defined by modified PICaSSO [Paddington International Virtual ChromoendoScopy ScOre], Mayo Endoscopic Score [MES] and probe-based confocal laser endomicroscopy [pCLE] with histological indices in UC. Methods: A prospective study enrolling 82 UC patients [male 66%] was conducted. High-definition colonoscopy was performed to evaluate the activity of the disease with MES assessed with High-Definition MES [HD-MES] and modified PICaSSO and targeted biopsies were taken; pCLE was then performed. Receiver operating characteristic [ROC] curves were plotted to determine the best thresholds for modified PICaSSO and pCLE scores that predicted histological healing according to the Robarts Histopathology Index [RHI] and ECAP 'Extension, Chronicity, Activity, Plus' histology score. Results: A modified PICaSSO of ≤ 4 predicted histological healing at RHI ≤ 3, with sensitivity, specificity, accuracy and area under the ROC curve [AUROC] of 89.8%, 95.7%, 91.5% and 95.9% respectively. The sensitivity, specificity, accuracy and AUROC of HD-MES to predict histological healing by RHI were 81.4%, 95.7%, 85.4% and 92.1%, respectively. A pCLE ≤ 10 predicted histological healing with sensitivity of 94.9%, specificity of 91.3%, accuracy of 93.9% and AUROC of 96.5%. An ECAP of ≤ 10 was predicted by modified PICaSSO ≤ 4 with accuracy of 91.5% and AUROC of 95.9%. Conclusion: Histological healing by RHI and ECAP is accurately predicted by HD-MES and modified virtual electronic chromoendoscopy PICaSSO, endoscopic score; and the use of pCLE did not improve the accuracy any further.